The effect of gamma irradiation on the chemical structure and surface characteristics of dipalmitoylphosphatidylcholine (DPPC) [Kesan sinaran gama ke atas struktur kimia dan ciri permukaan dipalmitoilfosfatidilkolina (DPPC)] - Mohd H.M.K.; Ahmad A.F.; Mohamed F.; Kamaruzaman N.S.; Ling N.W.; Jin P.R.; Yasir M.S.; Ramli S.; Radiman S.; Rahman I.A.; Mohd Hafez Mohd Isa (2024)
Indexed by Scopus